Kompetensi Pedagogik Guru PAK dalam Penerapan Metode Demonstrasi pada Siswa SD di Tapanuli Utara. - Marlince Simanjuntak (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the pedagogical competence of Christian Religious Education teachers in implementing the demonstration method to students at SD Negeri 173182 Lobutolong, North Tapanuli Regency. The pedagogical competence in question includes the teacher's ability to design, implement, and evaluate effective learning, focusing on the demonstration method used to improve students' understanding and skills. This study is a descriptive qualitative approach. The subjects of this study were Christian Religious Education teachers at SD Negeri 173182 Lobutolong, as well as several students who were directly involved in the learning process. The study results indicate that Christian Religious Education teachers at SD Negeri 173182 Lobutolong have good pedagogical competence in implementing the demonstration method. Teachers can use the demonstration method effectively to teach Christian religious concepts, such as compassion, forgiveness, and other moral values, by actively involving students in the learning process. Applying the demonstration method positively impacts the learning process and the formation of student character. Therefore, schools need to continue to increase support for the development of teacher competence and the provision of facilities that support the optimal implementation of this method.